The Political Economy of Redistributive Social Security - Pestieau, Pierre (IMF Working Papers; Working Paper ;, 1999)
Population aging puts significant pressure on social security systems that are based mainly on a pay-as-you-go (PAYG) formula and determined by the political process in which both retirees and future retirees participate. This paper demonstrates that in an economic and demographic steady state, majoritarian democracy overspends on social security. It then shows that in case of demographic shock, the regular majority process can be paralyzed by the development of entrenched interest groups that could lose from majority decisions. Depending on the way these entrenched interests operate, they can be judged more or less desirable from the viewpoint of social justice.